Similarity search and applications : 10th International Conference, SISAP 2017, Munich, Germany, October 4-6, 2017, Proceedings /: 10th International Conference, SISAP 2017, Munich, Germany, October 4-6, 2017, Proceedings. (2017) - Unknown
No abstract available